Exercise, Sports, and Cardiac Rehabilitation Recommendations in Patients with Aortic Aneurysms and Post-Aortic Repair: A Review of the Literature - Michael Stiefel; Hadassa Brito da Silva; Christian Marc Schmied; David Niederseer (Journal of Cardiovascular Development and Disease)
Introduction: Balancing the well-documented benefits of regular exercise, particularly its positive impact on cardiovascular risk factors like hypertension, with the potential risks for patients with aortic aneurysms presents a significant challenge. This narrative review aims to summarize the current evidence and guidelines to assist clinicians in making informed exercise and sports recommendations for patients with aortic aneurysms or post-aortic repair. Methods: Nine clinical trials on the effect of exercise on abdominal aortic aneurysms (AAAs) were identified, including one study on cardiopulmonary exercise testing (CPET) in AAA patients. As no clinical trials on exercise in thoracic aortic aneurysms (TAAs) were found, we extrapolated data from other studies on exercise in aortic diseases, including data from patients who have had an aortic dissection, as well as three studies on cardiac rehabilitation (CR) and one study on CPET after proximal aortic repair. Review articles and guidelines were also incorporated to ensure a comprehensive overview of the topic. Results: Currently, no clear correlation exists between intense sports activities and the development of aortic aneurysms or dissections. Conclusions: Light to moderate physical activity appears safe and beneficial for patients with aortic aneurysms and post-aortic repair. Given the lack of evidence linking athletic activity to aortic complications, caution is warranted in restricting such activities for athletes, underscoring the importance of shared decision-making. Regular follow-up and optimal management of cardiovascular risk factors are essential.